2013
DOI: 10.1063/1.4799624
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic (Ga,Mn)As nanowires grown by Mn-assisted molecular beam epitaxy

Abstract: (Ga,Mn)As nanowires were grown by molecular beam epitaxy using Mn as a growth catalyst on GaAs(001) substrates at 485 °C, i.e., at intermediate temperatures higher than ones used for the growth of (Ga,Mn)As thin films, but lower than the ordinary temperatures of Au-assisted growth of GaAs nanowires. (Ga,Mn)As nanowires obtained with typical lengths between 0.8 and 4 μm and diameters 50–90 nm do not have defects, such as dislocations or precipitates, except for the stacking faults lying parallel to the growth d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
3
13
0
1
Order By: Relevance
“…In such conditions lighter (Ga,Al)As appear darker. STEM images taken along the [11][12][13][14][15][16][17][18][19][20] zone axis permit to determine clearly the interfaces between different shells along the NW length. The tomography was performed with the following parameters: electron probe size 0. paramagnetic test sample) are achieved by degaussing the magnetometer with an oscillating magnetic field of decreasing amplitude.…”
Section: Tem Imaging and Elemental Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…In such conditions lighter (Ga,Al)As appear darker. STEM images taken along the [11][12][13][14][15][16][17][18][19][20] zone axis permit to determine clearly the interfaces between different shells along the NW length. The tomography was performed with the following parameters: electron probe size 0. paramagnetic test sample) are achieved by degaussing the magnetometer with an oscillating magnetic field of decreasing amplitude.…”
Section: Tem Imaging and Elemental Mappingmentioning
confidence: 99%
“…7 These options are all well encompassed within a bottom-up approach: a controlled growth of ferromagnetic nanowires of (preferably) semiconductor origin, may serve as an ideal route to provide the necessary architecture and resulting functionalities. This is predominantly the reason of the strong ongoing interest in the elaboration of nonequilibrium growth of (Ga,Mn)As dilute ferromagnetic semiconductor (DFS) nanowires (NWs) [8][9][10][11][12][13][14][15][16][17][18][19][20][21] which would exhibit or even surpass the excellent micromagnetic properties of the prototype, epitaxial (Ga,Mn)As layers. 22 This challenge has proven to be a formidable one.…”
Section: Introductionmentioning
confidence: 99%
“…5 They can also be doped with magnetic impurities, 6,7 while the large difference between the temperatures suitable for the growth of GaAs NWs and for the incorporation of Mn as substitutional impurities makes the growth of (Ga,Mn)As NWs challenging. 8 As (Zn,Mn)Te can be doped strongly p-type so that ferromagnetism appears and transport studies are feasible in 2D, 9 ZnTe-based NWs are attractive for a basic study of spintronics mechanisms in 1D. In addition, CdTe quantum dots can be incorporated and used as a single photon source 10 or as a very sensitive optical probe of the spin properties.…”
mentioning
confidence: 99%
“…17 In accordance to the results of structural investigation of samples with 5 (In,Mn)As QD layers, the study of their optical properties has not revealed any specific features due to the presence of defects described above. At the same time, the PL spectra of the samples containing 3 (In,Mn)As QD layers exhibited the presence of spectral lines which can be caused not only by the radiation from (In,Mn)As QDs (see QD3 in Figure 2(a)) but also by Mn ions replacing Ga cation's position in GaAs matrix 17,25,26 (see e-A 0 Mn peak in Figure 2(a)). Similar to the investigation of the circular polarization of the structure with one (In,Mn)As QD layer, 17 the results obtained for the QD3 PL band of the sample with 3 QD layers exhibit a nonlinear dependence of the circular polarization, which was saturated at q c $ 0.03 in an applied magnetic field H ¼ 5 T. After rescaling, this dependence (see solid circles in Figure 2(b)) coincides with one measured on e-A 0 Mn band (see solid squares in Figure 2 polarization in comparison with e-A 0 Mn band can be related to the confinement effect on Mn acceptor state.…”
mentioning
confidence: 93%